Accountability for Presentation of Financial Statements Based on ISAK No. 35 with Maqashid Syariah Perspective: Case Study on Khusnul Yaqin Wage Orphanage Foundation - Dewy Titik Murtosyiah; M. Dliyaul Muflihin; Ade Irma Suryani Lating; Nandha Nur Jagadhitawati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This study examines the